A comparison of muscle electromyographic activity during different angles of the back and front squat - Trindade, T. B.; de Medeiros, J. A.; Dantas, P. M. S.; de Oliveira Neto, L.; Schwade, D.; de Brito Vieira, W. H.; Oliveira-Dantas, F. F. (Isokinetics and Exercise Science, 2020)
BACKGROUND: Many different squatting techniques have been recommended, but few studies tried to identify how different muscle groups contributed to this movement in each technique. OBJECTIVE: To compare the electromyographic activation (EMG) of the thigh, hip and trunk muscles during maximal voluntary isometric contractions in the back and front squat performed in different degrees of knee flexion, while also comparing the levels of force produced during different ranges of motion. METHODS: Ten healthy men (30.7 ± 7.9 years), regularly practicing strength training, performed maximal isometric actions during back and front squats, at 60 ° , 90 ° and 120 ° degrees of knee flexion. The electromyographic activity of the rectus femoris, vastus lateralis, vastus medialis, biceps femoris, gluteus maximus, and erector spinae was recorded. RESULTS: At 60 ° a lower EMG activation in both squats was observed although this depth showed the highest levels of maximal voluntary isometric strength. Increasing knee flexion to 120 ° did not result in greater muscle activation. Only at 90 ° there was no significant difference in EMG activity between the front and back squat. CONCLUSIONS: A greater squat depth did promote a decrease in EMG activity When executed in isometric contraction, parallel squatting offers better ratio of force X recruitment of primary motor muscles. Therefore, this amplitude can be used in training or rehabilitation strategies, both in frontal and posterior variations (with higher level of strength), observed the most convenient option for the practitioner.